Pacientka se třemi EGFR mutacemi - postupný rozvoj rezistence na předchozí cílenou léčbu - Svatoň, Martin; Pešek, Miloš; Baxa, Jan; Mukenšnabl, Petr; Benešová, Lucie; Minárik, Marek (Klinicka onkologie, 2017)
BACKGROUND: Patients with sensitive EGFR mutations are already being treated with first and second generation tyrosine kinase inhibitors (TKIs). However, resistance to these drugs occurs over time, and over half of all cases is caused by a mutation (T790M) in the EGFR kinase domain. Osimertinib offers a new treatment option that overcomes this problem. Unfortunately, resistance to this drug also develops after several months of treatment and is caused by another mutation (C797S) in EGFR. CASE REPORT: Our case report provides evidence for the progressive development of EGFR-TKI resistance in a patient with a deletion of exon 19 in the EGFR gene. First, based on a mutation (T790M) identified after afatinib treatment and a subsequent mutation (C797S) mutation identified after osimertinib treatment. We mention overcoming this resistance (C797S) mutation by using 4th generation EGFR-TKI and other alternative procedures (chemotherapy, immunotherapy, and combinations of older EGFR-TKI generations). We also mention a rare case of peritoneal metastasis that occurred after previous treatment with osimertinib that we attempted to ameliorate by using erlotinib because the impaired condition of the patient did not allow treatment by chemotherapy. There are documented cases in which erlotinib has been successfully given to patients with peritoneal metastases and patients with the EGFR mutation C797S following progression to afatinib. This was not the case in our patient, probably because of the remaining EGFR mutation T790M. CONCLUSION: In our case report, erlotinib did not show efficacy after progression to osimetinib. Nowadays, chemotherapy is the only possible treatment in patients with good a performance status. The next-generation of TKIs are undergoing promising developments.Key words: EGFR - deletion on exon 19 - mutation T790M - mutation C797S - afatinib - osimertinibSubmitted: 12. 9. 2017Accepted: 12. 10. 2017 This project was supported by grant AZV 17-30 748A. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.
Keywords: Acrylamides; aniliny; Drug Resistance, Neoplasm; piperaziny; ErbB Receptors; inhibitory proteinkinas; akrylamidy; Piperazines; Mutation; erbB receptory; afatinib; Protein Kinase Inhibitors; Aniline Compounds; Erlotinib Hydrochloride; chemorezistence; lidé; Humans; mutace; erlotinib; Afatinib